Complications and outcome in left-sided endocarditis in children - Alehan, Dursun; Özkutlu, Süheyla; Ayabakan, Canan; Bilgiç, Arman; Özme, Şencan; Özer, Sema; Çeliker, Alpay (The Turkish Journal of Pediatrics, 2002)
We retrospectively assessed the clinical course and outcome of left-sided endocarditis in pediatric patients to find out the prognostic significance of the presence and size of echocardiographically detected vegetations. Among the children admitted to our institution with endocarditis between January 1987 and October 1999, 16 patients (mean age 9.03 ± 4.95 years) who met the Duke criteria for the diagnosis of infective endocarditis (IE) were included in this study. Rheumatic valvular disease was the most frequent underlying heart disease (10 patients: 62.5%). Five patients were operated at a mean of 13.9 months before endocarditis, and all had residual defects. Vegetation was detected in 11 cases (69%). Ten patients had major complications (within 2 weeks in 6 patients). Three patients developed congestive heart failure (CHF), six had intracranial and one had lower extremity emboli. Among them four were operated because of complications (CHF: 3 cases, intracranial emboli: 1 case). All the operated cases are doing well. The association between intracranial embolic events and echocardiographically detected vegetations was determined by calculating specificity (40%), sensitivity (100%), positive predictive value (50%), and negative predictive value (100%). No intracranial embolism occurred in patients without vegetations. All vegetations were ≤ 6 mm in patients with systemic embolism. There were four deaths, three of which were because of intracranial embolism. This study suggests that intracranial emboli have a major risk of mortality in left-sided endocarditis. The larger size of the vegetation is not a predictor of complications; furthermore, the absence of vegetations predicts that the patient is safe from embolic events. Therefore all patients with left-sided IE should be considered for earlier surgical intervention.